2000
DOI: 10.1051/parasite/2000072071
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors and the distribution of mansonelliases in Southern Venezuela

Abstract: Summary:The distribution of mansonelliases and their relation to various quantitative criteria were determined through the study of 1,057 subjects in 17 localities in ten regions of Amazonas State and Bolivar State. The total prevalence among the blood samples, determined through the Knott technique, was 1 8.54 %. 1 1.26 % were parasited by Mansonella perstans, 9.93 % by Mansonella ozzardi, and 2.63 % by both species. The average of microfilaremia was 48.19 mf/mL of blood in /VI. perstans and 13.79 mf/mL in M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
7
0
2
Order By: Relevance
“…Prevalence rates from other studies in West and Central Africa demonstrate a similarly wide infection rate, ranging from 3.2% to 47% in Nigeria (Agbolade and Akinboye, 2001; Akogun, 1992; Anosike et al, 1992, 2005b; Arene and Atu, 1986; Udonsi, 1986, 1988; Ufomadu et al, 1991; Useh and Ejezie, 1995) and 6.0% in Sierra Leone (Gbakima and Sahr, 1996) to 49.1% in Gabon (Van Hoegaerden et al, 1987), 66.3% in Guinea (Vila Montlleo, 1990), and 75% in Mali (Keiser et al, 2003). The only recent study from Latin America was conducted among an indigenous population in Venezuela and found a prevalence of 11.3% (Gómez and Guerrero, 2000). A study from Colombia found a prevalence of 6% in affected communities in the 1980s (Kozek et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence rates from other studies in West and Central Africa demonstrate a similarly wide infection rate, ranging from 3.2% to 47% in Nigeria (Agbolade and Akinboye, 2001; Akogun, 1992; Anosike et al, 1992, 2005b; Arene and Atu, 1986; Udonsi, 1986, 1988; Ufomadu et al, 1991; Useh and Ejezie, 1995) and 6.0% in Sierra Leone (Gbakima and Sahr, 1996) to 49.1% in Gabon (Van Hoegaerden et al, 1987), 66.3% in Guinea (Vila Montlleo, 1990), and 75% in Mali (Keiser et al, 2003). The only recent study from Latin America was conducted among an indigenous population in Venezuela and found a prevalence of 11.3% (Gómez and Guerrero, 2000). A study from Colombia found a prevalence of 6% in affected communities in the 1980s (Kozek et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…In the past ten years, the results of cross-sectional studies from Brazil (Cohen et al, 2008; Garrido and Campos, 2000; Medeiros et al, 2008), Bolivia (Bartoloni et al, 1999), and Venezuela (Gómez and Guerrero, 2000) have been published. Most of the studies in Brazil and Venezuela were conducted in communities located along rivers in the Amazon basin and focused on indigenous groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidenciamos la presencia de mosquitos Culicoides sp., los cuales están relacionados con la transmisión de la mansonelosis, en particular, como lo demuestra un estudio en el norte de Argentina en el que se compara el grado de infectividad de los diversos vectores a M. ozzardi; también 6 , en una región del estado de Bolívar (Venezuela), encontraron una prevalencia de filariosis de 18,5%, donde evidenciaron que la transmisión en la zona fue de M. ozzardi por el vector Simulium y del vector Culicoides para la transmisión de M. perstans. Fernandez et al 17 , entre el 2004 y 2006 en el municipio de Paunini, del estado de Amazonas (Brasil), encontraron filariosis en el 24,9%, donde evidenciaron la presencia de simúlidos en diferentes comunidades del estudio.…”
Section: Discussionunclassified
“…ozzardi is located in the forest areas of the Amazon Basin [14] and the Orinoco Basin [15] where there are small foci scattered along the banks of the rivers. The countries concerned are Northern Brazil [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], the three Guianas : French Guiana [34], Surinam [35] and Guyana [36,37], Venezuela [15,[38][39][40][41], Eastern Colombia [42][43][44][45], and Northeastern Peru [46,48].…”
Section: On the South American Continentmentioning
confidence: 99%